How to Operationalize Gender Issues in Country Work. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2018)
Reducing gender gaps can have important economic benefits. Gender gaps remain significant on a global scale, both with respect to opportunities and outcomes. For example, gender-based legal restrictions in many parts of the world, as well as barriers in access to education, healthcare, and financial services, prevent women from fully participating in the economy. In turn, labor force participation rates are lower among women than men. Gender equality can play an important role in promoting economic stability by boosting economic productivity and growth, enhancing economic resilience, and reducing income inequality. The Fund has begun operationalizing gender issues in its work. Staff has contributed to the economic literature through country-level and cross-country analytical studies, confirming the macro-criticality of gender issues in a broad set of circumstances. Gender issues are also increasingly becoming an integral part of capacity development though technical assistance and training. And in country work, two waves of gender pilots have been completed-encompassing both surveillance and Fund-supported programs and covering all regions of the world and all levels of income-and a third wave is under way. Coverage of gender issues in staff reports should be selective and calibrated to the degree of macroeconomic significance. All teams should consider whether gender issues are relevant, taking into account also the authorities' priorities, but with no presumption that gender issues will be covered everywhere or every year and with in-depth coverage anticipated in only a limited number of cases any year. Staff should point to macroeconomic significance where it exists, with analysis focused on aspects with economic implications and specific policy advice limited to areas where there is Fund expertise. Where relevant, country teams should leverage external expertise. This note provides an overview of good practices and resources available to staff. The note is consistent with the 2015 Guidance Note for Surveillance Under Article IV Consultations and draws also on the 2013 Guidance Note on Jobs and Growth Issues in Surveillance and Program Work. It provides examples of good practice with respect to coverage of gender issues in country reports and lays out the resources available to country teams, both with respect to existing analytical work as well as the availability of data and tools.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet